Unintended consequences and trade‐offs of fish passage. Issue 4 (3rd September 2012) - McLaughlin, Robert L; Smyth, Eric R B; Castro‐Santos, Theodore; Jones, Michael L; Koops, Marten A; Pratt, Thomas C; Vélez‐Espino, Luis‐Antonio
Abstract: We synthesized evidence for unintended consequences and trade‐offs associated with the passage of fishes. Provisioning of fish passageways at dams and dam removals are being carried out increasingly as resource managers seek ways to reduce fragmentation of migratory fish populations and restore biodiversity and nature‐like ecosystem services in tributaries altered by dams. The benefits of provisioning upstream passage are highlighted widely. Possible unwanted consequences and trade‐offs of upstream passage are coming to light, but remain poorly examined and underappreciated. Unintended consequences arise when passage of native and desirable introduced fishes is delayed, undone (fallback), results in patterns of movement and habitat use that reduce Darwinian fitness (e.g. ecological traps), or is highly selective taxonomically and numerically. Trade‐offs arise when passage decisions intended to benefit native species interfere with management decisions intended to control the unwanted spread of non‐native fishes and aquatic invertebrates, or genes, diseases and contaminants carried by hatchery and wild fishes. These consequences and trade‐offs will vary in importance from system to system and can result in large economic and environmental costs. For some river systems, decisions about how to manage fish passage involve substantial risks and could benefit from use of a formal, structured process that allows transparent, objective and, where possible, quantitative evaluation of these risks. Such a process can also facilitate the design of an adaptive framework that provides valuable insights into future decisions.